2015
DOI: 10.18295/squmj.2015.15.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs Related to Diabetes Mellitus Prevention among Adolescents in Saudi Arabia

Abstract: abstract:Objectives: The incidence of type 2 diabetes mellitus (T2DM) is growing rapidly in the Saudi population. The purpose of this study was to assess the constructs of the health belief model (HBM) as they relate to T2DM lifestyle and prevention behaviours among adolescents. Methods: A cross-sectional study was conducted between May and October 2013 among 426 non-diabetic secondary school students from randomly selected schools in Riyadh, Saudi Arabia. An Arabic version of an adapted English language quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…Some reported reasons were shared with other parts of the world, while others were specific to the Arab region. It is clear that the hot climate of the Arabian Peninsula and Gulf countries limits outdoor physical activity to relatively short seasons and requires special indoor facilities [ 13 , 38 , 44 52 ]. In addition in most countries, the built environment, inadequate public transportation systems, and lack of spaces for walkers or joggers discourage exercise [ 15 , 20 , 26 , 31 , 38 , 42 , 46 , 47 , 53 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reported reasons were shared with other parts of the world, while others were specific to the Arab region. It is clear that the hot climate of the Arabian Peninsula and Gulf countries limits outdoor physical activity to relatively short seasons and requires special indoor facilities [ 13 , 38 , 44 52 ]. In addition in most countries, the built environment, inadequate public transportation systems, and lack of spaces for walkers or joggers discourage exercise [ 15 , 20 , 26 , 31 , 38 , 42 , 46 , 47 , 53 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition in most countries, the built environment, inadequate public transportation systems, and lack of spaces for walkers or joggers discourage exercise [ 15 , 20 , 26 , 31 , 38 , 42 , 46 , 47 , 53 68 ]. As in other studies, time constraints were mentioned as barriers [ 15 , 26 , 28 , 30 , 31 , 40 42 , 46 , 52 , 54 , 67 , 69 – 73 ], in addition to insufficient motivation or interest [ 25 , 26 , 34 , 44 , 46 , 54 , 71 , 73 ], other priorities [ 26 ], and lack of skills [ 26 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study of 426 non-diabetic secondary school students, the authors found higher obesity rates in males than females ( p =0.013). 20 The male students were also less aware of the risks of T2DM, such as obesity, family history, and high fat intake. The students acknowledged obesity as the most important risk factor, while weight reduction was recognized as the key preventive measure.…”
Section: Resultsmentioning
confidence: 99%
“…Food decisions inclined toward the higher Energy food. 17 There are four causes play the greater part developing chronic diseases, principally absence of physical exercise, poor nourishment, tobacco utilization, and excessive alcohol intake. Chronic diseases can be prevented by following certain dietary habits.…”
Section: Introductionmentioning
confidence: 99%